2007
DOI: 10.1007/s11064-007-9355-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ageing and the Beneficial Role of α-Lipoic Acid

Abstract: Oxidative damage has been implicated to be a major causative factor in the decline in physiological functions that occur during the ageing process. Mitochondria are known to be a rich source for the production of free radicals and, consequently, mitochondrial components are susceptible to lipid peroxidation (LPO) that decreases respiratory activity. In the present investigation, we have evaluated mitochondrial LPO, 8-oxo-dG, oxidized glutathione, reduced glutathione, ATP, lipoic acid, TCA cycle enzymes and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…Pérez et al (2008) showed a decrease in mitochondrial function characterized by a reduction in ATP production from isolated mitochondria and a reduction in the activity of the electron transport chain complexes using mice heterozygous for mitochondrial thioredoxin 2 gene, along with increased ROS production compared to wild type mice, increased oxidative damage to nuclear DNA, lipids, and proteins and more apoptosis in liver. Palaniappan and Dai (2007) and Savitha and Panneerselvam (2007) It is obvious from the previous reports that mitochondria must have a robust endogenous antioxidant enzyme system which can be potentially affected during ageing. Among them, mitochondrial Mn-SOD, peroxiredoxins such as PRDX5, glutathione peroxidase (GPx), and HSP are involved.…”
Section: Mitochondrial Dysfunctions In Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pérez et al (2008) showed a decrease in mitochondrial function characterized by a reduction in ATP production from isolated mitochondria and a reduction in the activity of the electron transport chain complexes using mice heterozygous for mitochondrial thioredoxin 2 gene, along with increased ROS production compared to wild type mice, increased oxidative damage to nuclear DNA, lipids, and proteins and more apoptosis in liver. Palaniappan and Dai (2007) and Savitha and Panneerselvam (2007) It is obvious from the previous reports that mitochondria must have a robust endogenous antioxidant enzyme system which can be potentially affected during ageing. Among them, mitochondrial Mn-SOD, peroxiredoxins such as PRDX5, glutathione peroxidase (GPx), and HSP are involved.…”
Section: Mitochondrial Dysfunctions In Ageingmentioning
confidence: 99%
“…The term ''mitochondrial nutrient'' (Liu 2008) refers to a group of agents that can directly or indirectly protect mitochondria from oxidative damage and improve mitochondrial function (Long et al 2007;Liu 2008;Palaniappan and Dai 2007;Savitha and Panneerselvam 2007;Plecitá-Hlavatá et al 2009). Direct protection includes preventing the generation of oxidants, scavenging free radicals and inhibiting oxidant reactivity, removing oxidized inactive proteins accumulation (Musicco et al 2009), elevating cofactors of defective mitochondrial enzymes, and also protecting enzymes from further oxidation.…”
Section: Mitochondria-targeted Chemopreventionmentioning
confidence: 99%
“…α-Lipoic acid is commonly used as a dietary supplement by athletes to increase muscle glucose uptake, improve antioxidant defense, and decrease oxidative damage level. However, most studies concerning the beneficial effects of α-lipoic acid on cell metabolism were observed in in vitro studies or animal models, such as rodents and horses [5][6][7][8][9]. …”
mentioning
confidence: 99%
“…Forster and associates also found such behavioral deficit in old mice which correlates to the protein oxidation and impaired energy metabolism [44]. Therefore, on the basis available evidences, it may be stated that an impaired TCA cycle and electron transport chain functioning in aged rats may lead to decreased ATP production, resulting in changes in motor functioning, perturbed memory status and other neurobehavioral changes [45].…”
Section: Discussionmentioning
confidence: 99%